2013
DOI: 10.1111/hex.12102
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of Czech dental patients to the use of rubber dam

Abstract: Background The most frequent arguments against rubber dam are that patients generally do not like it and the prolonged time of treatment. However, according to several studies, the attitude of patients towards rubber dam is rather positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 10 publications
7
18
3
4
Order By: Relevance
“…In our study, gender difference was found to have no statistically significant influence on patients' acceptance of RD. These findings were in agreement with those of Kapitan's study 11 , but in contrast to the finding of Stewardson's 13 and Vadavathi's 12 studies, where females had higher levels of acceptance of RD. Age was also found to have no influence on the level of acceptance; this was similar to the findings of Kapitan .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, gender difference was found to have no statistically significant influence on patients' acceptance of RD. These findings were in agreement with those of Kapitan's study 11 , but in contrast to the finding of Stewardson's 13 and Vadavathi's 12 studies, where females had higher levels of acceptance of RD. Age was also found to have no influence on the level of acceptance; this was similar to the findings of Kapitan .…”
Section: Discussionsupporting
confidence: 91%
“…One of the reported barriers to the use of RD by dentists worldwide is patients' discomfort and incompliance 4,5 . The results of our study and many other studies 11,12,13 showed high levels of acceptance and positive attitudes towards treatment with the RD isolation, especially when they were educated about its importance and benefits during treatment. Based on these findings, we could say that lack of patient compliance is not an acceptable reason for not using this tool of isolation during operative or endodontic procedures.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The questionnaire was designed based on questionnaires used in similar studies by different authors [23,[26][27][28][29]. The questionnaire was translated to Arabic language and back to English by two independent professional translators to avoid any translation errors.…”
Section: Methodsmentioning
confidence: 99%